Відображення елементів української національної ідеї в науковій творчості М.І.Костомарова - Пінчук, Ю.А. (Український історичний журнал, 2007)
У статті здійснено науковий огляд дисертації видатного ученого, письменника і громадського діяча Миколи Костомарова (1817-1885) «О причинах и характере унии в Западной России», інших розвідок, що є знаковими не тільки в його творчості як історика, а й у вітчизняній історіографії в цілому. Акцентується увага на відображенні елементів української національної ідеї. The author of the article has made a scientific review of the dissertation of the dissertation of the outstanding scholar, writer and public figure Mykola Kostoma¬rov (1817-1885) «On the reasons and character of the unia in Western Russia» as well as of the other studies which became hallmarks not only in Kostomarov’s creative work as a historian, but also in national historiography as a whole. The article emphasizes the elements of the Ukrainian national idea, presented within the context of the retrospective and perspective of Ukraine’s history.